Tecnologia e gamificação na prática do ensino de filosofia: a experiência com olimpíadas filosóficas - Pereira, Murilo Fernando (2024)
This work aims to present the importance of discussing the use of technology in the teaching of philosophy, as well as to make the learning of philosophy more engaging for students by proposing gamification and the use of local philosophical olympiads as teaching methodologies. The practical proposal of the olympiads was implemented with high school students from a public school, utilizing apps, digital platforms, text readings, debates, text creation, and other resources, with the purpose of awakening interest in philosophy. The results obtained so far are positive, showing a significant improvement in student performance and greater engagement in the proposed activities. The work also highlights the importance of the critical use of technology in philosophy teaching, as young people are increasingly familiar with such technological resources. The research aims to contribute significantly to the debate on the ethical use of technology in philosophy teaching and the use of new learning methodologies, particularly concerning local olympiads.